The temporal trend of road traffic mortality in China from 2004 to 2020 - Kehao Ren; Lipeng Miao; Juncheng Lyu (Elsevier, 2023)
Background: Road traffic accidents are one of the critical disasters that cause massive negative influences to the social economy and people's property, health and life safety. The purpose of this study is to analyze the temporal trend of road traffic mortality in China from 2004 to 2020, and further analyze the key factors that the influencing changes in China's road traffic mortality and provides information for the development of targeted interventions to reduce the number of preventable deaths. Methods: The data were retrieved from the Chinese Death Cause Monitoring Data Set from 2004 to 2020. The road traffic mortality rates were standardized by the Sixth National Population Census (6th NPC) data. Joinpoint regression method was manipulated to analyze temporal trends of standardized road traffic mortality. The study used annual percentage change (APC) and average annual percentage change (AAPC) calculated by the Joinpoint regression model to describe trends in road traffic mortality rates. Results: The overall age-adjusted road traffic mortality in China showed a declining trend from 2004 to 2020 (AAPC2004-2020 = - 4.2%), from 20.9 to 12.92 per 100,000. Rural road traffic mortality rates were generally higher than the one in urban areas, and males were generally higher than females. There was an overall downward trend of the standardized road traffic mortality in the East and Central regions between 2004 and 2020. It was worth noting that the road traffic mortality rates in the Western region showed an upward trend from 2006 to 2011 (APC2006-2011 = 3.3%) and continued to decline after 2011 (APC2011-2020 = - 6.7%). The road traffic mortality rates of aged 65 years and older was highest, which required focused attention. Conclusions: From 2004 to 2020, the road traffic mortality rates in China generally declined. At the same time, there was a slow reduction or even an upward trend in road traffic mortality rates among the elderly and in western regions. Rural males are a priority group for road traffic injury prevention.